Estado nutricional de crianças nordestinas: estudo de algumas variáveis úteis à vigilância nutricional - Mello, Alvaro Antônio Cabral Vieira de (1996)
The nutricional status is an indicator which synthesizes the conditions of life, it show the social-economics, environmental and biological conditions, presenting great sensíbility to the floatation’s of these conditions. Its mensuration and the analysis of its causing factors are capable to identify those malnourished either those in risk of malnutrition, it becomes then very useful to select the risk groups which deserves better attention from society. In the Northeast of Brazil we may fínd the highest prevalence of malnutrition in the world. The hunger is a so common feature that it went into a banalization process. The objectives of this study were: to define the profile of the malnourished child in the Northeast of Brazil, from the database of the National Research for Health and Nutrition in 1989; to evaluate the risk of malnutrition associated to others variables such social-econornical and environmental, taking in account the urban and rural situation and comparing the nutritional status with the south of Brazil analyzing the utility of those variables in stabilizing the risk of malnutrition, in order to contribute indirectly to the nutritional vigilance. It was studied 2.103 children in the Northeast and 1.407 in the south, the band age was 0 to 5 years old. In the Northeast the prevalence of malnutrition was 30% to the percent < 3 and 46,2% to the percent < 10 from the pattern of National Center Health Statistic (NCHS), to the urban area 23,4% and 36,9%, to the rural area 34,6% and 52,6% respectively. The variables which show association with the nutritional status and that may be useful to the nutritional vigilance were: per capita household income, water supply, sewer supply, mother ílliteracy and the number of residents per house. The variables which didn't show association with malnutrition were: mother working out, mother being the head of the family and electrical energy supply.